Load-carrying capacity and failure mode of composite steel-concrete truss element under monotonic loading. Issue 1 (December 2020) - Wariyatno, Nanang Gunawan; Haryanto, Yanuar; Han, Ay Lie; Gan, Buntara Sthenly; Sudibyo, Gathot Heri
Abstract: Composite steel-concrete trusses are among the most economical systems for building, particularly for greater spans, allowing proper internal space utilization without limiting columns. This paper examines 12 lab tests on two types of composite steel-concrete truss elements compared with the conventional steel truss element as a control specimen. The experiments investigate the load-carrying capacity of the truss element with different configurations under monotonic loading. The study on the specimen's failure modes was based on the welded joints. The obtained results were compared with analytical evaluations of typical resisting mechanisms of steel-concrete composite, reinforced concrete, and steel structures with updated Indonesian design codes. The basic features of the steel-concrete truss elements discussed quantitatively and qualitatively.